Dark Alphabet - Maier, Jennifer, 1961- (Book collections on Project MUSE., 2006)
In works whose subjects range from the religious to the carnal, the whimsical to the foreboding, Jennifer Maier's debut collection of poems, Dark Alphabet, explores the everyday mysteries of our common experience with humor, lucidity, and an unblinking yet compassionate eye. Whether occasioned by a song overheard on the car radio, a packet of risque postcards from the 1920's, a conversation with a dead parent, or the behavior of ducks in mating season, each poem sets off on a journey that ranges far from its origins, arriving with the reader in a clearing at dusk.